Strategi Navigasi Perempuan Tani Tunakisma Di Kecamatan Konda dalam Menghadapi Dinamika Sosial Ekonomi Lokal - Syaifudin Suhri Kasim; Aryuni Salpiana Jabar; Lutfiana Nur Azizah; Megawati A. Tawulo; Ratna Supiyah; Suharty Roslan (Jurnal Neo Societal, 2025)
This research aims to describe the navigation strategies of homeless women farmers in dealing with local socio-economic dynamics in Konda District, South Konawe Regency. This research uses a descriptive qualitative approach to explore the navigation strategies of homeless women farmers in dealing with local socio-economic dynamics in Konda District, South Konawe Regency. This approach was chosen because it allows for an in-depth exploration of the experiences, perspectives and strategies applied by women farmers in dealing with the challenges they face. Data collection techniques were carried out through in-depth interviews, participant observation and documentation, using qualitative descriptive analysis. The results of the research show that the navigation strategies of homeless women farmers in facing local socio-economic dynamics are carried out through: developing social networks, resource management skills, revenue strategy , as well as household economic diversification strategies. In fact, the household economic diversification strategy is an effective adaptive approach for homeless women farmers in facing local socio-economic dynamics. By utilizing local skills, managing risks and creating alternative income, they are able to increase the economic resilience of their families. However, the success of this strategy is highly dependent on inclusive policy support, access to resources, and reduction of structural barriers. Through economic diversification, women farmers not only survive economic challenges but also contribute to social development and community empowerment at the local level.